Modelagem da economia paralela na América Latina - Veiga, Fernando Cavalcante (2017)
This dissertation estimates the size and evolution of the shadow economy in 18 Latin American countries, from 1990 to 2013, using the Multiple Indicators and Multiple Causes (MIMIC) model. It is noted that increases in regulatory intensity, opening of the economy, money supply and GDP per capita lead to grow the shadow economy, while investment growth tends to decrease it. The results obtained point to an average shadow economy of 35.6% of the official GDP in Latin America, with a tendency of growth during the studied period, a behavior that is also verified when fuzzy logic based estimation is used. With percentages below 28%, countries such as Chile, Argentina and Costa Rica contribute in a way to reduce the average of the region. Panama, Bolivia and Honduras, countries with the highest levels of informality, raise the average. The only Latin American country to register a decline in the shadow economy over the analyzed period is Venezuela.